The effectiveness of promotional tools adopted by CIMB Wealth Advisors (CWA) towards their sales performance / Noor Syuhada Masroh and Muhamad Hafizuddin Hamdani - Masroh, Noor Syuhada; Hamdani, Muhamad Hafizuddin (Faculty of Business and Management, 2015)
The purpose of this study is to identify The Effectiveness of Promotional Tools Adopted by CIMB Wealth Advisors (CWA) towards their sales performances. CIMB Wealth Advisors as known as CWA is CIMB Bank subordinate company that serve unit trust funds together with protection plans, trust nomination and estate planning solutions. The sale performance of CWA has been fluctuated and one of the contributions is the promotional tools. The promotional tools adopted by CWA are advertising, direct marketing, personal selling and sales promotions. Advertising in CWA has been advertised on the newspaper, brochures, banner, pamphlets and the fund fact sheet give enough information about the CWA’s product. Direct marketing has been work out by doing the telemarketing and direct e- mail. The personal selling has been done by doing the road show and face to face meeting with the customers. Moreover, CWA has offer rebate and some wonderful free gift to the customers to encourage the purchasing. We have obtained the objectives of this study as the guide to get the final solutions to the problems statement. The study has been conduct by collect the important data. Questionnaires have been distributed to 150 of target population which is the customers of CWA in Melaka Raya. 150 questionnaires haves been distributed to the respondents who came to CWA in Melaka Raya and some of them who we met during rod show. However, only 133 of questionnaires were return back. The data collected has been analyzed using the SPSS to know the Cronbach’s Alpha by using the reliability test; determine the significant relationship by doing the Correlation analysis and Regression analysis to know which promotional tools contributes most to the sales performance of CWA. The findings that obtained from this study shows that advertising, direct marketing and personal selling have significant relationship with CWA’s sales performance while the sales promotion do not has the significant relationship but still has positive relationship with the sales performance. The Regression analysis has shown that the advertising contributed the most towards the sales performances of CWA and then followed by the direct marketing and the personal selling on the second and third places respectively. The least contributes to the sales performance of CWA is the sales promotion. Hence, the objectives of this study have been achieved.